Written Corrective Feedback Given to Errors in Sentence Structure: A Case Study - Fabiola Gunady (Institute of Research and Community Outreach - Petra Christian University, 2018)
This study is done to find out the types of written corrective feedback related to errors in sentence structure given by the teacher of Writing 2 class and the types of sentence structure errors that have written corrective feedback. In this study, I used two theories: a typology of written corrective feedback types proposed by Ellis (2009) and exploring errors in grammar proposed by Ho (2005). This research used qualitative approach. The source of data was 23 students’ original drafts after the midterm exam and the data are teacher’s written corrective feedback found in the students’ original drafts and sentence structure errors that have written corrective feedback. The findings of this study showed that there were three types of written corrective feedback found in the students’ original drafts, namely: Direct Corrective Feedback, Indirect Corrective Feedback, and Reformulation and there were five types of sentence structure errors found in the students’ original drafts, namely: Fragmented sentence, Run-on sentence, Inappropriate coordinating conjunction, Inappropriate subordinating conjunction, and Misordering or Inversion of subject-verb.